A randomized controlled trial of infraorbital block using ketamine 1% for intra- and postoperative analgesia in children for ambulatory cleft lip correction (Faculty of Medicine Universitas Indonesia, 2021)
BACKGROUND In Indonesia, cleft lip correction surgery is often done as a social program in remote areas with limited resources. This study aimed to assess the effectiveness of ketamine, a cheaper and more accessible alternative, as a local analgesia in infraorbital block and to determine the possibility of ketamine as an alternative local analgesic drug for intraoperative and postoperative periods. METHODS This was a randomized controlled trial in children aged 2 months to 5 years who underwent cleft lip correction surgery at Cipto Mangunkusumo Hospital in 2016. Subjects were randomly divided into two groups: ketamine and bupivacaine. Standard general anesthesia with endotracheal intubation was performed in each group. Bilateral intraoral infraorbital block was performed using ketamine 1% 0.5 ml or bupivacaine 0.25% 0.5 ml. Postoperative evaluation includes pain scores based on the face, leg, activity, cry, and consolability (FLACC) scale and analgesic duration. RESULTS A total of 36 subjects were enrolled in this study, with 18 in each group. Both groups received the same total amount of fentanyl addition intraoperatively (p = 1). The postoperative FLACC pain scale scores between the two groups were not different, with p>0.05 in every measurement. The mean duration of postoperative analgesia in the ketamine group was longer than the bupivacaine group (15–13.49 hours, p = 0.031). CONCLUSIONS Infraorbital block with 1% ketamine 0.5 mg/kg was similarly effective for intraoperative and postoperative analgesia but had a longer duration than that with 0.25% bupivacaine 0.5 ml in ambulatory cleft lip correction.